2019
DOI: 10.1002/slct.201803783
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Chelated Biopolymer Coated Mesoporous Silica Nanoparticles as Highly Efficient, Stable, and Recyclable Nanocatalysts for Catalytic Bleaching

Abstract: The role of catalysts in the development of improved bleaching methods is of paramount scientific and industrial importance in the bleaching of raw cotton and laundry stains. Despite tremendous efforts, developing novel earth abundant metal nanocatalysts with high activity and stability remains a great challenge. Here, we demonstrate the successful formation of earth abundant transition metal‐chelated layer‐by‐layer hyaluronic acid/chitosan polyelectrolyte‐coated mesoporous silica nanoparticles (Metal@PEM‐MSNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In comparison, the rate constants of morin achieved with Ru/C-dots are much higher than those obtained with other metal NPs-based catalysts, which signify the superior catalytic performance of Ru/C-dots toward morin. Meijboom et al reported the catalytic evaluation in the oxidation of morin with individual Au, Pd, and Pt NPs encapsulated by dendrimer. They have found rate constants of 0.0009, 0.0038, 0.0015, and 0.0003 s –1 for Au-DENs, Pd-DENs, Pt-DENs, and PdAu-DENs-OH, respectively. Recently, Xiao et al and Yu et al have reported the catalytic oxidation of morin by biocompatible dendrimer-encapsulated Pd NPs and bovine serum albumin-stabilized Pt NPs, respectively. , Similarly, mesoporous structured nanocatalysts including Co/Sn oxide- and transition-metal (Mn 2+ , Fe 2+ , and Co 2+ )-chelated biopolymer-coated silica nanoparticles were applied to the oxidation of morin. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the rate constants of morin achieved with Ru/C-dots are much higher than those obtained with other metal NPs-based catalysts, which signify the superior catalytic performance of Ru/C-dots toward morin. Meijboom et al reported the catalytic evaluation in the oxidation of morin with individual Au, Pd, and Pt NPs encapsulated by dendrimer. They have found rate constants of 0.0009, 0.0038, 0.0015, and 0.0003 s –1 for Au-DENs, Pd-DENs, Pt-DENs, and PdAu-DENs-OH, respectively. Recently, Xiao et al and Yu et al have reported the catalytic oxidation of morin by biocompatible dendrimer-encapsulated Pd NPs and bovine serum albumin-stabilized Pt NPs, respectively. , Similarly, mesoporous structured nanocatalysts including Co/Sn oxide- and transition-metal (Mn 2+ , Fe 2+ , and Co 2+ )-chelated biopolymer-coated silica nanoparticles were applied to the oxidation of morin. , …”
Section: Resultsmentioning
confidence: 99%
“…42 45,46 Similarly, mesoporous structured nanocatalysts including Co/ Sn oxide-and transition-metal (Mn 2+ , Fe 2+ , and Co 2+ )-chelated biopolymer-coated silica nanoparticles were applied to the oxidation of morin. 47,48 The mechanism was proposed for the catalytic oxidation of morin, as shown in Scheme 2. The absorption peaks observed at 267 and 394 nm corresponding to the π−π* transitions are assigned to the conjugated system of rings A and B in connection with ring C, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, different metal nanoparticles have been used as active catalysts in catalytic oxidation since they possess several unique properties, like easy synthesis, high surface area, distinctive optical behaviors, easy removal from the reaction environment, considerable dispersion in the solutions, etc. 4,[10][11][12][13][14][15] Among other transition metal nanoparticles, silver nanoparticles (AgNPs) are particularly useful in oxidation processes because of their exceptional properties, such as high catalytic activity, long-term stability, small sizes, and special optical features. 14,[16][17][18][19][20] The first report on the catalytic evaluation of AgNPs as oxidation nanocatalysts in the presence of H 2 O 2 was published by Meijboom et al 21 In their manuscript, they presented the preparation and characterization of poly-(amidoamine) (PAMAM)-stabilized AgNPs and their catalytic activity in the degradation of morin.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the reversible effects arising from dynamic covalent bonds (transesterification reaction, disulfide bond, Diels–Alder reactions, etc.) and noncovalent supramolecular interactions (hydrogen bonding, , metal coordination, host–guest interactions, ,, and π–π stacking interactions) have been achieved. Dichtel et al fabricated an acid-degradable polycarbonate material with recyclability based on trans-carbonation exchange chemistry, having a high tensile strength (36 MPa) and Young’s modulus (∼1 GPa).…”
Section: Introductionmentioning
confidence: 99%